Melatonin supplementation improves the intactness of plasma membrane and acrosomal membrane of cryopreserved spermatozoa in Hariana bull - YADAV, DILEEP KUMAR; KUMAR, ANUJ; SAXENA, ATUL; SWAIN, DILIP KUMAR (The Indian Journal of Animal Sciences, 2019)
Supplementation of MT @ 2 mM was more beneficial in cryopreservation of Hariana bull spermatozoa as evidenced from post-thawed sperm membrane integrity and acrosomal intactness. Melatonin can be recommended to be used @ 2 mM concentration into the semen extender to increase the post thaw sperm functional attributes in Hariana bull.